Membidik Pertautan Teologis antara Tubuh dan Ibadah Menurut Roma 12:1 - Blegur, Romelus (Studia Philosophica et Theologica, 2024)
The orientation of the body to worship God through worship is an important principle in Christianity because it is for this purpose that humans were created by God. However, the problem that is immediately faced is the emergence of various discourses about the body which tend not to open up space for connectivity between the body and worship as a meaningful relationship for human existence as religious beings. The problem is that the body is often seen as a material object that is mortal and does not contain any special qualities in the practice of worship. Even if the body is useful, it is only a means that is limited in time and space. The aim of this research is to question this perspective based on the text Romans 12:1 and target the theological connection between the body and worship in their respective specialties. This research uses a library research method by investigating through literature selected according to the objectives of this research and supported by hermeneutics as a method of interpreting biblical texts. The results of this research show that the theological link between the body and worship is visible through the destination of the body and the continuity of worship which is eternal or eternal. This is what allows the offering of the body to become a manifestation of true worship to God.